Unraveling the characteristics of geopolymer mortars: A deep dive into the impact of marble powder as fine aggregate and varied activators - Bilir, Turhan; Aygormez, Yurdakul; Bastan, Zeynep; Uysal, Mucteba; Aygun, Beyza Fahriye (ELSEVIER SCI LTD, 2024)
This study addresses the literature gap by investigating the durability effects of potassium activators in metakaolin (MK) and granulated blast furnace slag (GBFS) based geopolymer mortars (GMs), particularly in freezingthawing cycles and sulfate resistance. It explores enhancing GMs ' strength and sustainability with marble powder (MP). The research evaluates GMs ' resilience against high temperatures, freezing -thawing cycles, and sulfate exposure by assessing binders, activators, molarity optimization, and mechanical properties. Using NaOH+Na 2 SiO 3 and KOH+K 2 SiO 3 activators, GM formulations began with a 100% RILEM sand series (6 -12 M). Compressive, flexural strength and UPVs were assessed at 7, 28, and 90 days. Optimal ratios were 0.9 for sodiumactivated GMs and 0.8 for potassium -activated GMs. Maintaining a consistent 50% MK and 50% GBFS binder, MP was added to the mixture with optimum molarity. Using RILEM sand as a fine aggregate, GMs exhibited an optimum molarity of 10 M. Surpassing 50% MP adversely affected strength. Both activators excelled in the 100% RILEM sand series, reaching 45 MPa compressive strength at 28 days and 50 MPa at 90 days. High -temperature analyses showed a decrease at 300 degrees C compared to the 90 -day series, and the compressive strength of KOH+K 2 SiO 3 -activated GMs increased at 600 degrees C. Analyses at 900 degrees C revealed significant reductions, exacerbated by MP replacing RILEM sand. Freezing -thawing and sulfate resistance tests negatively impacted GMs when replacing RILEM sand with MP, with the KOH+K 2 SiO 3 activator having a more pronounced influence. Incorporating MP into GMs enhances performance and promotes sustainable production, offering benefits in both performance and environmental aspects.
Keywords: Geopolymers; Activators; Marble powder; Mechanical properties; Durability properties; HYDRATION PROCESS; PORTLAND-CEMENT; CONCRETE; METAKAOLIN; BEHAVIOR; SLAG; ENVIRONMENT; EMISSIONS; Construction & Building Technology; Engineering; Materials Science